Informed options trading prior to insider trades. Issue 3 (1st February 2021) - Hao, (Grace) Qing; Li, Keming
Abstract: We find abnormal volatility spreads in the options market immediately before corporate insider stock trades, suggesting informed options trading prior to insider trades. The informed options trading is more pronounced for large insider trades, firms in more corrupt areas, and insider purchases in firms with high information asymmetry. Furthermore, the abnormal volatility spreads are positively associated with the post‐trade abnormal returns. In the aftermath of the Securities and Exchange Commission's squawk box cases, informed options trading before insider trades mostly disappeared except for a group of insider stock sales related to insider derivatives transactions such as employee stock options exercises.